2010
DOI: 10.1189/jlb.0610327
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PD-L1 and PD-L2 on human macrophages is up-regulated by HIV-1 and differentially modulated by IL-10

Abstract: PD-1 plays an important role in T cell exhaustion during HIV infection. PD-1 has two ligands: PD-L1, expressed on hematopoietic and nonhematopoietic cells, and PD-L2, limited to DCs and macrophages. Little is known about PD-L1 expression and regulation in human macrophages. Previous reports have found few immediate effects of macrophage exposure to HIV, suggesting that macrophages lack PRRs for this virus. Using quantitative confocal microscopy and a multiplexed cytokine bead array, we measured induction of PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
81
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 39 publications
10
81
2
Order By: Relevance
“…In addition, chronic immune activation leads to the upregulation of inhibitory molecules and is widely believed to be one of the driving forces of immune exhaustion, in which effector cells lose their function and proliferation capacities (4,(24)(25)(26)(27)(28)(29)(30). Here we show, for the first time to our knowledge, that activation and exhaustion markers such as HLA-DR, CD38, PD-1, and TIM-3 are elevated in humanized BLT mice chronically infected with HIV-1 ( Figure 1A) and that CD8 T cells expressing multiple suppressive receptors such as PD-1 and TIM-3 define an exhausted effector T cell population ( Figure 1B) as observed in human HIV patients (1,14) and mice chronically infected with LCMV (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, chronic immune activation leads to the upregulation of inhibitory molecules and is widely believed to be one of the driving forces of immune exhaustion, in which effector cells lose their function and proliferation capacities (4,(24)(25)(26)(27)(28)(29)(30). Here we show, for the first time to our knowledge, that activation and exhaustion markers such as HLA-DR, CD38, PD-1, and TIM-3 are elevated in humanized BLT mice chronically infected with HIV-1 ( Figure 1A) and that CD8 T cells expressing multiple suppressive receptors such as PD-1 and TIM-3 define an exhausted effector T cell population ( Figure 1B) as observed in human HIV patients (1,14) and mice chronically infected with LCMV (3).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular immune responses in HIV-infected NOD SCID common γ chain-deficient (NSG)/humanized bone marrow-human fetal liver and thymus (BLT) mice (NSG-BLT mice) have been recently demonstrated to closely mirror those in humans (4,(24)(25)(26)(27)(28)(29)(30), making it a good model to study HIV immune pathology and immune-based therapies in vivo. To investigate immune activation and immune exhaustion in vivo, we generated NSG-BLT mice (for representative flow plots of human lymphocytes, see Supplemental Figure 1; supplemental material available online with this article; doi:10.1172/ JCI89488DS1) and mock-infected or infected mice with HIV-1 and followed the expression of the immune inhibitory receptors PD-1 and TIM-3 and the activation markers HLA-DR and CD38 on CD8 + and CD4 + T cells (for representative staining of the markers, see Supplemental Figure 2).…”
Section: Expression Of Exhaustion and Activation Markers Is Elevated mentioning
confidence: 99%
“…This molecule can deliver signals that inhibit T-cell activation and proliferation. 11,12 Human monocytes in the peripheral blood can be divided into the following three subsets: CD14 dim CD16 1 (non-classical monocytes), CD14 high CD16 1 (intermediate monocytes) and CD14 high CD16 2 (classical monocytes). 13,14 Each subset has a unique genetic signature and distinct functions regarding inflammation and the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of HIV infection per se on PD-1 ligand expression is less clear; most studies have analysed the expression of these ligands in antigen presenting cells. It has been found that PD-L1 and PD-L2 can be induced in monocytes/macrophages after exposure to competent and inactivated HIV (Rodriguez-Garcia et al, 2011). PDL1 could be preferentially up-regulated in macrophages in an anti-inflammatory environment and PD-L2 might be predominantly up-regulated in a pro-inflammatory environment (Rodriguez-Garcia et al, 2011).…”
Section: Ajidmentioning
confidence: 99%
“…It has been found that PD-L1 and PD-L2 can be induced in monocytes/macrophages after exposure to competent and inactivated HIV (Rodriguez-Garcia et al, 2011). PDL1 could be preferentially up-regulated in macrophages in an anti-inflammatory environment and PD-L2 might be predominantly up-regulated in a pro-inflammatory environment (Rodriguez-Garcia et al, 2011). HIV infection could also induce the expression of PD-L1 in DC (Muthumani et al, 2011).…”
Section: Ajidmentioning
confidence: 99%